Prevalence of Bullying Victimization among School-Going Adolescents in Secondary Schools in Al-Karkh, Baghdad, Iraq - Hyder M. Yahya; Mushtaq T. Hashim; Eman A. Al-Kaseer; Jawad K. Al-Diwan (Current Progress in Arts and Social Studies Research Vol. 8, 2024)
Background: Bullying victimization is a major public health problem. Interest in bullying in the Arab world is a recent phenomenon. In the last four decades, Iraq was exposed to wars, civil war, widespread violence and sectarian violence which in turn means unrest community, internally displaced families (low affluence) and high exposure to trauma. Publication on victimization in Iraq is limited. Purpose: This study was conducted to report bullying among students of Iraqi schools. Methods: A total of 302 students from Baghdad were selected by a cluster random sample to include in this study. Participated students were recruited by multistage random sampling. An Arabic version of the standardized questionnaire was obtained from the International (ISPCAN). Identification of bullying (bullies, victims and sexual victims) was done by using a cutoff for the scoring of bullying manifestation in the questionnaire depending on three repeated actions at least to consider as bullies. Chi-square was used to examine the association of victimization and sexual victimization (dependent variable) with sex, smoking and drug abuse (independent variable). P value less than 0.05 was considered significant for meeting the criteria of bullying. Results: Out of the total 39.1% were bullied pupils (victims) there was a significant association between bullying and victim with sex (P=0.001). A significant difference was noticed in age between those who reported sexual victimization and those who reported no sexual victimization. Bullying and victimization were significantly associated with smoking, drug abuse, and failure in school (P=0.001 for each). Conclusion: A high prevalence of victimization (bully, victims and sexual victim was revealed among students in schools as a predictor for smoking and drug abuse.